PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATEMATIKA BERBASIS MASALAH UNTUK KELAS IX SMP/MTs PADA POKOK BAHASAN BARISAN DAN DERET - -, Juliati; Eka Afri, Lusi (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2016)
The purpose ofÂ  the research was toÂ  produced studentâs worksheets that based valid problem and sequence and series practical comprehension. The research was used about Research and Development itâs consisted of three phase. They wereÂ  defining, designing and developing. The researchâs subject was students grade IX at MTs Fathul Anwar 2015/2016 year. The instrument used validation sheet and question were practical. It has Processed to based valid and practicalÂ  thoroughÂ  defining phase, designing phase and developing phase. Worksheets development had valided by 4 validators andÂ  got about 3,18 validation grade in the phase. While practical got try out and evaluation used practical quisioner by expert had got 77,5 % mark result practically.Â  Practical try outÂ  by teacher had gotÂ  84,09% mark result.Â  With best practically. Studentâs try out had got 84,13 % mark result with their best practically atÂ  MTs Fathul AnwarÂ  grade IX.Â  There fore the conclusion of the worksheet had based valid problem and best practically.